Systems of financial analysts training - Moklyachuk, M.; Yamnenko, R.; Borysenko, O. (Інститут математики НАН України, 2007)
A review of different systems of ﬁnancial analysts training which exist in European countries and the United States of America is proposed. MBA diploma and professional qualiﬁcation such as Chartered Financial Analyst designation (CFA) in the United States of America, or Certiﬁed International Investment Analyst designation (CIIA) in Europe and Asia, are required for ﬁnancial analysts to get certain level within a ﬁrm. We consider in details qualiﬁcation levels that are offered by the most famous institutions such as Faculty of Actuaries and Institute of Actuaries (UK), Chartered Financial Analyst Institute (USA), Association of Certiﬁed International Investment Analysts, Association of Corporate Treasurers (UK). In Ukraine an equivalent international qualiﬁcation can be obtained in the Training Center for Actuaries and Financial Analysts.